Physical cryptography and security of digital devices - A. A. Ivaniuk; S. S. Zalivaka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article presents the main scientific results and practical achievements obtained by undergraduate and graduate students of Computer Science department of BSUIR under the supervision of professor A.A. Ivaniuk during the period from 2014 to 2018. The original circuit solutions in the field of synthesis of digital physically unclonable functions are presented. The area of physically unclonable functions was first time published in the journal «Informatics» by professor of Software for information technologies department of BSUIR, doctor of technical sciences V.N. Yarmolik, which is a famous domestic scientist in area of reliable digital devices and systems design. New methods and algorithms for unclonable identification and authentication of digital devices are described. The paper also presents the results obtained in the field of random number sequences generation. In addition, the results on the methods of hardware watermarks injection and functional obfuscation of digital devices are given.